Long Term Results of a Rotating Hinge Total Knee Prosthesis With Carbon-Fiber Reinforced Poly-Ether-Ether-Ketone (CFR-PEEK) as Bearing Material - Vertesich, Klemens; Staats, Kevin; Böhler, Christoph; Koza, Richard; Lass, Richard; Giurea, Alexander (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Background The use of rotating hinge (RH) prostheses for severe primary as well as revision arthroplasty is widely established. Due to the steadily increasing number of RH prostheses, we aimed to assess the complication frequencies, complication types and clinical outcomes of a modern RH hinge prosthesis using a new bearing material with a minimum follow-up of 7 years. Methods Fifty-six consecutive patients who received the EnduRo® RH prosthesis using carbon-fiber reinforced poly-ether-ether-ketone (CFR-PEEK) as bearing material were included in this prospective study: 21 patients (37.5%) received the prosthesis as a primary total knee arthroplasty (TKA) and 35 patients (62.5%) underwent revision total knee arthroplasties (rTKA). Clinical and radiographic examinations were performed preoperatively, postoperatively after three and twelve months and annually thereafter. Clinical scores were documented for each patient. Competing risk analysis was assessed with respect to indication and failure mode. Results Knee Society Score (KSS), Western Ontario and McMaster Osteoarthritis Index (WOMAC), Oxford Knee Score (OKS) and range of motion (ROM) improved significantly compared to preoperative values (p < .0001). The overall cumulative incidence for revision surgery was 23.6% at 7 years and the cumulative incidence for complications associated with failure of the prothesis was 5.6% at 7 years, respectively. Complications occurred more frequently in the revision group (p=.002). Conclusion The evaluated RH prosthesis provided reliable and durable results for a minimum follow-up of seven years. Prosthesis survival was successful considering the complexity of the cases. The use of this RH system in primary patients showed high survival rates and long-term functional outcomes and clinical outcomes proved to be satisfying in both revision and primary cases. No adverse events were associated with the new bearing material CFR-PEEK.